The Impact of TikTok Technology Transformation in the Digitalization Era Using SmartPLS - Murni, Cahyasari Kartika (Journal of Informatics Development, 2023)
The utilization of technology has become the foundation for many businesses striving to remain competitive in the current digital era, where online shopping is increasingly dominant. TikTok, as a popular social media platform, has been employed as a marketing tool to reach a wider audience by offline businesses. This research seeks to understand the impact of TikTok technology utilization on online purchasing decisions. The sustainability of offline businesses depends on adapting to the changing consumer behavior, which is increasingly inclined towards online shopping. This study highlights the importance of using TikTok as a creative and innovative marketing tool to reach online customers. The research results indicate that the more intensive the use of TikTok technology, the more likely customers are to opt for online shopping. Subsequently, the ease of shopping on TikTok mediates the influence of technology utilization on online purchasing decisions. However, online product prices do not play a significant mediating role in purchase decision-making. In order to compete in an increasingly interconnected digital era, offline businesses need to consider more innovative marketing strategies and focus on providing a better user experience. The utilization of technology and creativity in TikTok content becomes the key to influencing online purchase decisions by digitally connected customers.